Peningkatan Kemampuan Kompetensi Matematika Pendidikan Dasar melalui Pendekatan Investigasi Berbantuan Manipulatif - Agus Susanta Susanta (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2021)
Mathematical competence abilities of elementary education students play an important role in the success of learning mathematics in elementary schools. The purpose of this study was to describe an increase in students' understanding of mathematical concepts through a manipulative assisted investigative approach. The research subjects were students of the first semester elementary  teachers education postgrade students who took Elementary  education mathematics courses in the 2019/2020 academic year. This research is a classroom action research using data collection methods in the form of observation and tests results. Furthermore, the data were analyzed using data reduction and data triangulation. The results showed that the application of investigative learning increased the ability to understand deep mathematical concepts. The manipulative assisted mathematical investigative approach increases students in carrying out exploration, making assumptions, and making conclusions.